2009
DOI: 10.1590/s1519-69842009000300023
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of parasites of fish from the Upper Paraná River floodplain, Brazil

Abstract: The aim of the present study was to provide a current survey of the species of parasites found in the Upper Paraná River floodplain, as well as to investigate which strategies and mechanisms used by parasites, are favored and which environmental factors influence the parasite community in the studied environments. During a seven-year period from February 2000 to September 2007, 3,768 fish belonging to 72 species were collected and analyzed for the purpose of studying the parasite fauna. A total of 337 species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
135
3
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(150 citation statements)
references
References 16 publications
5
135
3
7
Order By: Relevance
“…These studies can indicate the fish food habit, as has been reported by Machado et al (1996), Takemoto et al (2004Takemoto et al ( , 2009 and Martins et al (2009). Piscivorous fish occupy the top of the food web and may present more chance of infection (Machado et al, 1996;Martins et al, 2009), while omnivorous fish present lower risks of infection by the fact that they are primary consumers in the food web (Feltran et al, 2004;Takemoto et al (2009).…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…These studies can indicate the fish food habit, as has been reported by Machado et al (1996), Takemoto et al (2004Takemoto et al ( , 2009 and Martins et al (2009). Piscivorous fish occupy the top of the food web and may present more chance of infection (Machado et al, 1996;Martins et al, 2009), while omnivorous fish present lower risks of infection by the fact that they are primary consumers in the food web (Feltran et al, 2004;Takemoto et al (2009).…”
Section: Introductionmentioning
confidence: 77%
“…An important characteristic of the monogenoideans is that of their host specificity (Takemoto et al, , 2009Thatcher, 2006), also serving as a taxonomic indicator. Parasites of the genus Cosmetocleithrum are mostly found in Siluriformes fish (Krytisky et al, 1986), mainly Doradidae and Pimelodidae (Suriano and Incorvaia, 1995;Thatcher, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Brazil, A. compactum metacercariae have been reported in several fish species (Santos et al, 2002;Machado et al, 2005;Yamada et al, 2008;Takemoto et al, 2009;Zica et al, 2009Zica et al, , 2011Paes et al, 2010a, b), and were recently found in G. proximus from the Nova Avanhandava Reservoir, Medium Tietê River, Brazil (Zica et al, 2010). In the present study, the prevalence of A. compactum in G. proximus was lower than that found by Zica et al (2010).…”
Section: Discussionmentioning
confidence: 96%